DEFAULT MORTGAGE CUSTOMERS THROUGH BANK KPR WITH BUYBACK GUARANTEE DEVELOPER FACILITY IN ISLAMIC ECONOMICS PERSPECTIVE - Suryadi, Djaka; Alim, Muhammad Nurul (Islamic Banking & Economic Law Studies (I-BEST), 2024)
This research aims to determine the buyback guarantee regulatory system and the buyback guarantee working mechanism until the bank makes a buyback guarantee claim to the developer. This research also aims to review buyback guarantee from Islamic perspective. The research method used is qualitative research using closed interviews and observation methods. Based on the research results, the developer has the criteria for potential partners to be able to work together and make agreement rules for both parties and the risks that will be experienced by the Customer, Bank, and Developer. The developer can make an effort before the bank makes a buyback guarantee claim to remind the customer that payment obligations at the bank are in arrears. In Islamic sharia perspective, the buyback guarantee is permitted provided that it is an option, not an obligation. The buyer may sell either to the first seller or another person. This provision is to avoid the prohibited bai’ al-'inah, which leads to prohibited riba transaction. Other Islamic solutions are debt restructuring (rescheduling) and postponement of the debt payment.The research is expected to give Islamic solution before buyback guarantee is executed